Physician emigration from Germany: insights from a survey in Saxony, Germany - Birte Pantenburg; Katharina Kitze; Melanie Luppa; Hans-Helmut König; Steffi G. Riedel-Heller (BMC, 2018)
Abstract Background Physician migration has been gaining attention worldwide. In Germany, physician migration became a topic of interest in the context of the discussion about a shortage of physicians, for which one contributing factor may be physicians leaving the country. However, there is a lack of literature on "push" factors causing German physicians to leave. The present study seeks to provide current data in an effort to promote the identification of "push" factors motivating German physicians to emigrate. Methods In a cross-sectional survey, all physicians ≤40 years of age registered with the State Chamber of Physicians of Saxony, Germany (n = 5956) were sent a paper-pencil questionnaire examining socio-demographics, job satisfaction, the wish to emigrate, and the likelihood of moving abroad in the near future. Variables associated with the wish to emigrate were assessed with multivariate logistic regression models. Results Approximately 30% of participants wished to emigrate. The favourite destination countries were Switzerland, Scandinavian countries, and Australia or New Zealand. Of participants wishing to emigrate, approximately 52% thought it likely to emigrate for a limited, and 15% for an unlimited period of time. Participants with the wish to emigrate were significantly less satisfied with their job situation as compared to physicians without the wish to emigrate, the one exception being their "relationship with patients". The three aspects with the highest difference in satisfaction were the overall work situation, followed by work load, and time for family, friends, and leisure activities. Being a woman, being in a relationship, and having children were associated with a lower chance for wishing to emigrate. Higher satisfaction with the factors "work load", "patient care", and "structural aspects" was also associated with a lower chance for wishing to emigrate. Conclusions Emigration seems to be a viable option for at least a subset of physicians. Preventive measures should address modifiable determinants associated with an increased chance for wishing to emigrate, such as job satisfaction. Especially satisfaction with the factor "work load" seems to play a crucial role as a "push" factor for physician emigration.